2015
DOI: 10.4155/fmc.15.90
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine–Oligonucleotide Conjugates: A Promising Direction for Nucleic Acid Tools and Therapeutics

Abstract: Chemical modification and/or the conjugation of small functional molecules to oligonucleotides have significantly improved their biological and biophysical properties, addressing issues such as poor cell penetration, stability to nucleases and low affinity for their targets. Here, the authors review the literature reporting on the biophysical, biochemical and biological properties of one particular class of modification - polyamine-oligonucleotide conjugates. Naturally derived and synthetic polyamines have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 104 publications
1
14
0
1
Order By: Relevance
“…Conjugation of variousa mino groups to oligonucleotides has been described by af ew groups. [24,25] In most cases, the 2'-OH group of ribonucleosides has been used to conjugate fragments onto antisense oligonucleotides, which placest he fragment into the minor groove upon hybridization withatarget, but generally does not produce large increases in binding affinity.W ef ound that the modification of short 2'-OMe oligoribonucleotides by conjugation of polyamine groups to the C5- positiono fu ridineb ases endowst hem with greatly increased target-binding affinity,c omparing favorably with state of the art bicyclic [9,10,25] and tricyclic nucleic acids. [50] The pioneering work of Pçrschke and Eigen led to the "nucleation-zipping" modeli nw hich the initial formation of three base-pairs represents the rate-limiting step in the hybridization of two complementary oligonucleotides, that is, an oligonucleotide drug and its RNA target.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conjugation of variousa mino groups to oligonucleotides has been described by af ew groups. [24,25] In most cases, the 2'-OH group of ribonucleosides has been used to conjugate fragments onto antisense oligonucleotides, which placest he fragment into the minor groove upon hybridization withatarget, but generally does not produce large increases in binding affinity.W ef ound that the modification of short 2'-OMe oligoribonucleotides by conjugation of polyamine groups to the C5- positiono fu ridineb ases endowst hem with greatly increased target-binding affinity,c omparing favorably with state of the art bicyclic [9,10,25] and tricyclic nucleic acids. [50] The pioneering work of Pçrschke and Eigen led to the "nucleation-zipping" modeli nw hich the initial formation of three base-pairs represents the rate-limiting step in the hybridization of two complementary oligonucleotides, that is, an oligonucleotide drug and its RNA target.…”
Section: Resultsmentioning
confidence: 99%
“…[1] The natural polyamines spermine and spermidine bind to and stabilizeR NAsi nc ells. [20][21][22][23][24] Recently,i tw as shown that polyamines conjugated to LNA oligonucleotidesh ad larger effects on target RNA binding. [16,17] In some cases polyamines (including oligospermines) [18,19] have been conjugated to oligonucleotides and have produced small increases in T M values (a few 8Cp er modification) with complementary RNA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1821 The polyamines have been attached either to the 5′, or the 3′ end of the ONs, (known as ZIP-ONs) 22, 23 with few reports for attachment to the nucleobases. 24, 25 In most cases, polyamine conjugation had beneficial effects on target hybridization, 26 nuclease resistance, and cellular uptake.…”
Section: Introductionmentioning
confidence: 99%